Mesenchymal stem cell containing tannin cerium nanoparticles as well as preparation method and application of mesenchymal stem cell

By combining tannin cerium nanoparticles with mesenchymal stem cells to form Ce-TA@BSA@MSC nanocomplex, the problems of bone tissue regeneration and anti-inflammatory aging in the treatment of periodontitis were solved, and the effects of alveolar bone protection and osteogenic differentiation were significantly improved.

CN119868411AInactive Publication Date: 2025-04-25SHANGHAI EAST HOSPITAL EAST HOSPITAL TONGJI UNIV SCHOOL OF MEDICINE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510070244.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing treatments for periodontitis cannot effectively promote bone tissue regeneration and anti-inflammatory aging, and mesenchymal stem cells are affected by oxidative stress in the inflammatory environment, limiting their therapeutic effects.

Method used

A mesenchymal stem cell containing tannin cerium nanoparticles was developed. By synthesizing cerium ions, tanninic acid, bovine serum albumin complex nanoparticles and combining them with mesenchymal stem cells, it forms Ce-TA@BSA@MSC nanocomplex, which is used to eliminate oxidative stress, inhibit inflammatory aging and promote osteogenic regeneration.

Benefits of technology

In the rat periodontitis model, this nanocomplex significantly protects the alveolar bone, inhibits bone resorption, improves the trabecular bone structure, reduces the expression level of proinflammatory factors, and increases the osteogenic differentiation potential of periodontal membrane stem cells, and alleviates inflammation-induced cellular senescence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868411A_ABST
    Figure CN119868411A_ABST
Patent Text Reader

Abstract

The invention discloses a mesenchymal stem cell containing tannin cerium nanoparticles. The mesenchymal stem cell is formed by compounding cerium ions, tannic acid, bovine serum albumin and mesenchymal stem cells. The invention also provides a preparation method of the mesenchymal stem cells containing the tannin cerium nanoparticles. The preparation method comprises a step of preparing a cerium ion, tannic acid and bovine serum albumin compound and a step of obtaining passage mesenchymal stem cells. And mixing the cerium ions, the tannic acid and the bovine serum albumin compound nanoparticles with a culture medium, then inoculating the mesenchymal stem cells into the culture medium containing the cerium ions, the tannic acid and the bovine serum albumin compound nanoparticles, and co-incubating to form the mesenchymal stem cells containing the tannin cerium nanoparticles. The invention also provides an application of the mesenchymal stem cell containing the tannin cerium nanoparticles in preparation of a medicine for treating periodontitis. The traditional Chinese medicine composition improves the treatment effect of periodontitis patients by removing oxidative stress, inhibiting inflammatory aging and promoting osteogenesis regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine and relates to a mesenchymal stem cell, specifically a mesenchymal stem cell containing tannin cerium nanoparticles and a preparation method and application thereof. Background Art

[0002] The treatment of periodontitis mainly relies on traditional periodontal treatment methods, including periodontal cleaning, antibiotic treatment, etc., but these methods are often unable to effectively promote bone tissue regeneration and anti-inflammatory aging. In addition, existing mesenchymal stem cell treatments are affected by oxidative stress in the inflammatory environment of periodontitis, limiting their therapeutic effects.

[0003] Although antioxidants are used to improve the cell microenvironment, there is no specific scheme to combine tannin cerium nanoparticles with mesenchymal stem cells. Existing anti-inflammatory therapies are still insufficient in dealing with oxidative stress and slowing down inflammatory aging. Summary of the invention

[0004] In view of the above technical problems in the prior art, the present invention provides a mesenchymal stem cell containing tannin cerium nanoparticles and a preparation method and use thereof. The mesenchymal stem cell containing tannin cerium nanoparticles and a preparation method and use thereof are intended to solve the technical problem that the drugs in the prior art are not effective in treating periodontitis.

[0005] The invention provides a mesenchymal stem cell containing tannin cerium nanoparticles, which is composed of cerium ions, tannic acid, bovine serum albumin and mesenchymal stem cells.

[0006] The present invention also provides a method for preparing the above-mentioned mesenchymal stem cells containing tannin cerium nanoparticles, comprising the following steps:

[0007] 1) Dissolving cerium salt and bovine serum albumin in ultrapure water, stirring and mixing, adding tannic acid, and adjusting the pH value to 8 to form cerium ion, tannic acid, bovine serum albumin composite nanoparticles (Ce-TA@BSA);

[0008] 2) a step of obtaining mesenchymal stem cells for passage, culturing the isolated mesenchymal stem cells in an α-MEM complete medium containing 10% by volume of fetal bovine serum, and performing passage when the cells reach 80%-90% confluence;

[0009] 3) The cerium ion, tannic acid, and bovine serum albumin complex nanoparticles of step 1) are mixed with α-MEM complete culture medium, and then the mesenchymal stem cells of step 2) are inoculated into the culture medium containing ions, tannic acid, and bovine serum albumin complex nanoparticles, and incubated for 12 to 36 hours to form mesenchymal stem cells containing tannin cerium nanoparticles (Ce-TA@BSA@MSC).

[0010] Furthermore, the cerium salt solution is Ce(NO3)3·6H2O.

[0011] The present invention also provides use of the mesenchymal stem cells containing tannin cerium nanoparticles in preparing medicine for treating periodontitis.

[0012] The present invention develops a mesenchymal stem cell (MSC) complex modified based on tannin cerium nanoparticles (Ce-TA@BSA NPs) to improve the therapeutic effect of periodontitis patients by clearing oxidative stress, inhibiting inflammatory aging and promoting osteogenesis regeneration.

[0013] The present invention synthesizes Ce-TA@BSA nanoparticles and combines them with MSCs to form Ce-TA@BSA@MSC nanocomplexes. This nanocomplex can effectively remove reactive oxygen species (ROS). Animal model experiments using the nanocomplex have verified that it has good effects in periodontal tissue regeneration, inflammation inhibition and osteogenic differentiation.

[0014] Compared with the existing technology, the technical effect of the present invention is positive and obvious. The present invention has verified through experiments that the Ce-TA@BSA@MSC nanocomposite shows a significant alveolar bone protection effect in a rat periodontitis model, effectively inhibits bone resorption, improves trabecular bone structure, and significantly reduces the expression level of pro-inflammatory factors. In addition, the nanocomposite can also significantly enhance the osteogenic differentiation potential of periodontal ligament stem cells (PDLSCs) and reduce inflammation-induced cell senescence. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The synthesis and characterization of nanoparticles (MSC and Ce-TA@BSA composite particles) are shown. 1A shows the TEM transmission electron microscopy of Ce-TA@BSA nanomaterials; 1B shows the elemental mapping; 1C shows the hydrodynamic diameter of Ce-TA@BSA nanoparticles; 1D shows the XPS graph of Ce-TA@BSA; 1E shows the high-resolution XPS graph of Ce 3d peak; 1F shows the C1s XPS spectrum of Ce-TA@BSA; 1G shows the Fourier transform infrared spectroscopy (FT-IR) analysis of Ce-TA@BSA; 1H shows the UV-visible spectrum of Ce-TA@BSA.

[0016] Figure 2 :Electron microscopic image of engineered mesenchymal stem cells.

[0017] Figure 3Micro-CT images show the changes in alveolar bone structure. (A) Experimental procedures for ligature-induced periodontitis and treatment regimens (PBS, Ce-TA@BSA, MSC, and Ce-TA@BSA@MSC). (B) Micro-CT analysis of the distance from cementum-enamel junction to alveolar bone crest (CEJ-ABC), bone volume fraction (BV / TV), trabecular thickness (Tb.Th), and trabecular separation (Tb.Sp) showed that the Ce-TA@BSA@MSC group significantly protected bone tissue. (C) Three-dimensional micro-CT images of alveolar bone morphology showed that bone height was restored in the Ce-TA@BSA@MSC group. (D) H&E staining (5X, 20X) showed that bone resorption was reduced and trabecular structure was improved in the Ce-TA@BSA@MSC group. (E) IL-1β immunohistochemical staining (5X, 20X) showed that inflammation was significantly reduced in the Ce-TA@BSA@MSC group. DETAILED DESCRIPTION

[0018] Example 1 Synthesis of Ce-TA@BSA

[0019] The synthesis of Ce-TA@BSA nanoparticles involves the addition of cerium ions (Ce 3+ / Ce 4+ ) combined with tannic acid (TA).

[0020] Dissolve cerium salt and bovine serum albumin (BSA) in ultrapure water, stir and mix, then add tannic acid TA. At this time, adjust the pH value to 8, and the solution color changes to dark brown, indicating that the nanoparticles are successfully formed. Continue stirring for 3 hours and then purify and dialyze to remove unreacted substances. The concentration of cerium ions in the final Ce-TA@BSA NPs production area is 371.68 mg / L. (Ce-TA complex is encapsulated in bovine serum albumin (BSA) to form Ce-TA@BSA nanoparticles).

[0021] The specific steps and methods are as follows:

[0022] 1) Ce-TA@BSA NPs were synthesized by a one-step self-assembly method: BSA (10 mg) and Ce(NO3)3·6H2O (6.25 mg) were dissolved in ultrapure water.

[0023] 2) Tannic acid (TA, 8.2 mg) was added to initiate the coordination-driven assembly process.

[0024] 3) Formation of Nanoparticles:

[0025] 4) Adjust the pH to 8 with NaOH, and the solution color turns dark brown, indicating that the nanoparticles are successfully formed. Stir at room temperature for 3 hours.

[0026] 5) Purification:

[0027] 6) The unreacted substances were then removed by 8 hours of dialysis, and the concentration of cerium ions in the final Ce-TA@BSA NPs production area was 371.68 mg / L.

[0028] 7) Ce-TA@BSA NPs were suspended in ultrapure water or buffer for subsequent use.

[0029] The experimental results are:

[0030] Figure 1 A shows the TEM image of Ce-TA@BSA NPs, revealing an irregular spherical morphology with an average particle size of ∼3.5 nm.

[0031] Elemental mapping by EDS ( Figure 1 B) The spatial uniform distribution of Ce and O elements is confirmed, with atomic fractions of Ce (3.94%) and O (96.06%). The Ce mass fraction reaches 26.41%, indicating that Ce is effectively incorporated into the nanoparticle matrix. The high oxygen content reflects the contribution of tannic acid and BSA, supporting the coordination between Ce ions and oxygen-containing groups.

[0032] Dynamic light scattering (DLS, Figure 1 C) Measurements show that the hydrodynamic diameter of Ce-TA@BSA NPs is ∼20 nm, which is larger than the size observed in TEM, likely due to the enhanced stability of the nanoparticles by the BSA coating.

[0033] XPS spectrum ( Figure 1 D) The composition and successful assembly of Ce-TA@BSA NPs are further verified with distinct peaks corresponding to Ce 3d, O 1s, and C1s elements at binding energies of 900, 533, and 285 eV, respectively.

[0034] Deconvolution of Ce 3D spectra ( Figure 1 E) reveals six peaks: three assigned to Ce 4+ (898, 882, 916 eV), three of which are assigned to Ce 3+ (903.8, 885, 900eV), get Ce 4+ / Ce 3+ The ratio is ~0.7. 3+ and Ce 4+ The presence of Ce is crucial for redox function because 4+ It can enhance the activity of catalase (CAT), while Ce 3+ It can increase the activity of superoxide dismutase (SOD).

[0035] FT-IR spectrum ( Figure 1F) shows the intensity of the hydroxyl-related peak (~1300 cm -1 ) decreases, reflecting the coordination between Ce ions and hydroxyl groups in TA.

[0036] UV-Visible Spectroscopy ( Figure 1 G) shows the characteristic absorption peak of BSA (~280 nm), confirming the successful surface functionalization. In addition, a red shift is observed compared to free TA, indicating that the structure changes after Ce coordination.

[0037] High-resolution C1s XPS spectra ( Figure 1 H) A major peak at 284.8 eV was identified, which was attributed to the unsubstituted carbon on the aromatic ring (CC), and a secondary shoulder at 286.8 eV corresponding to the CO or C=O bond. In addition, a broader peak at 290.9 eV was identified as the oscillating satellite of π-π*, which is characteristic of the aromatic rings on the surface of Ce-TA@BSA NPs. Peaks corresponding to CC (284.8 eV), CO / C=O (286.8 eV), and π-π* satellites (290.9 eV) are characteristic of aromatic groups in TA.

[0038] In summary, these results comprehensively establish the successful synthesis of Ce-TA@BSA NPs with integrated Ce 4+ / Ce 3+ valence state and stable coordination with TA and BSA.

[0039] Example 2 Cultivation of mesenchymal stem cells and methods for engineering stem cells

[0040] Mesenchymal stem cells (MSCs) were extracted from the placenta of healthy donors and cultured in α-MEM complete medium containing 10% fetal bovine serum by volume. When the cells reached 80%-90% confluence, they were passaged.

[0041] To combine Ce-TA@BSA nanoparticles with MSCs, Ce-TA@BSA nanoparticles were first mixed with α-MEM complete medium (from Gibco 12571063), and then MSCs were seeded into the medium containing Ce-TA@BSA nanoparticles. After co-incubation for 24 h, MSCs took up Ce-TA@BSA nanoparticles to form Ce-TA@BSA@MSC nanocomplexes.

[0042] The concentration of Ce ions in the purified Ce-TA@BSA buffer was 371.68 mg / L.

[0043] We first tested the cytotoxicity of nanoparticles to MSCs using CCK-8. The results showed that when the concentration of Ce ions was 6

[0044] μg / mL has the characteristics of promoting the proliferation of mesenchymal stem cells and has a good effect of clearing ROS. 5 Cells were seeded in 6-well plates at a density of 10 cells and allowed to adhere overnight. Cells were then treated with 6 μg / mL Ce-TA@BSA nanoparticles suspended in α-MEM medium and incubated for 24 hours at 37°C and 5% CO2. After incubation, cells were washed three times with phosphate-buffered saline (PBS) to remove unbound nanoparticles. Nanoparticle internalization was verified by transmission electron microscopy (TEM), and functional changes were assessed using immunofluorescence.

[0045] Transmission electron microscopy (TEM, Figure 2 ) showed that Ce-TA@BSA nanoparticles were successfully internalized by MSCs and evenly distributed in the cytoplasm. Notably, TEM images showed that the nanoparticles did not destroy the structure of intracellular organelles, demonstrating excellent biocompatibility. In addition, it was observed that Ce-TA@BSA nanoparticles were largely encapsulated in MSC-derived exosomes, indicating that the nanoparticles were secreted via the exosome pathway.

[0046] Example 3 Animal model establishment and treatment

[0047] The rat periodontitis model was induced by wire ligation at the first molars of the maxillary teeth on both sides of the rats to induce chronic inflammatory response and alveolar bone resorption. After 21 days of ligation, the rats were randomly divided into control group (Ctrl), PBS treatment group, Ce-TA@BSA treatment group, MSC treatment group and Ce-TA@BSA@MSC treatment group. Each group of rats received the corresponding treatment by local in situ injection. The treatment lasted for 7 days, with treatment every other day.

[0048] The therapeutic effect of Ce-TA@BSA@MSC nanocomposites was evaluated in a ligature-induced rat periodontitis model using micro-CT, histological, and immunohistochemical analyses ( Figure 3 A).

[0049] Micro-CT imaging showed that severe alveolar bone loss and trabecular structural destruction were observed in the PBS group, including a significant decrease in bone volume fraction (BV / TV) and trabecular thickness (Tb.Th), and an increase in trabecular separation (Tb.Sp), reflecting significant bone resorption. Although moderate bone protection was observed in the Ce-TA@BSA and MSC groups, Ce-TA@BSA@MSC treatment showed superior efficacy, significantly restoring BV / TV and Tb.Th, while significantly reducing Tb.Sp (p<0.001), close to normal levels. At the same time, the distance from the cementum-enamel junction to the alveolar bone crest (CEJ-ABC) in the Ce-TA@BSA@MSC group was significantly reduced, close to the healthy baseline level, indicating its ability to effectively alleviate bone loss ( Figure 3 BC).

[0050] Histological analysis further confirmed these findings by H&E staining. Severe structural destruction and bone resorption were observed in the PBS group, while partial protection was shown in the Ce-TA@BSA and MSC groups. In contrast, Ce-TA@BSA@MSC treatment restored alveolar bone morphology, showing a denser trabecular structure, while a decrease in epithelial hyperplasia and neutrophil infiltration was observed at the gingival junction, indicating that periodontal inflammation was significantly alleviated ( Figure 3 D).

[0051] The results of immunohistochemical staining also confirmed the anti-inflammatory effect of Ce-TA@BSA@MSC nanocomposites. In the PBS group, the expression of IL-1β was significantly increased; while in the Ce-TA@BSA and MSC groups, the expression of IL-1β was significantly decreased, among which the Ce-TA@BSA@MSC group had the largest decrease, close to the control group level ( Figure 3 E).

[0052] In summary, Ce-TA@BSA@MSC nanocomposites showed excellent protective effects in the rat periodontitis model. By protecting bone microstructure, inhibiting proinflammatory cytokines, and alleviating cell senescence, Ce-TA@BSA@MSC is expected to become a potential therapeutic strategy to alleviate bone loss and inflammation caused by periodontitis.

Claims

1. A mesenchymal stem cell containing tannin cerium nanoparticles, characterized in that: It is composed of cerium ions, tannic acid, bovine serum albumin and mesenchymal stem cells.

2. The method for preparing mesenchymal stem cells containing tannin cerium nanoparticles according to claim 1, characterized in that The steps include: 1) dissolving cerium salt and bovine serum albumin in ultrapure water, stirring and mixing, adding tannic acid, and adjusting the pH value to 8 to form cerium ion, tannic acid, and bovine serum albumin complex nanoparticles; 2) a step of obtaining mesenchymal stem cells for passage, culturing the isolated mesenchymal stem cells in an α-MEM complete medium containing 10% by volume of fetal bovine serum, and performing passage when the cells reach 80%-90% confluence; 3) The cerium ion, tannic acid, and bovine serum albumin complex nanoparticles of step 1) are mixed with α-MEM complete culture medium, and then the mesenchymal stem cells of step 2) are inoculated into the culture medium containing the ion, tannic acid, and bovine serum albumin complex nanoparticles, and incubated for 12 to 36 hours to form mesenchymal stem cells containing tannin cerium nanoparticles.

3. The method for preparing mesenchymal stem cells containing tannin cerium nanoparticles according to claim 2, characterized in that: The cerium salt solution is Ce(NO3)3·6H2O.

4. Use of the mesenchymal stem cells containing tannin cerium nanoparticles according to claim 1 in the preparation of a drug for treating periodontitis.

Citation Information

Patent Citations

  • Applications of mesenchymal stem cell and genetically modified mesenchymal stem cell

    CN103585177A

  • Active substance for treating periodontitis and preparation method and application thereof

    CN115969882A

  • Application of periodontal ligament stem cell-derived exosome in relieving cell senescence and treating periodontitis

    CN116251126A